Job stress and working conditions: Ireland in comparative perspective. An analysis of the European Working Conditions Survey - Helen Russell; Bertrand Maître; Dorothy Watson; Éamonn Fahey (The Economic and Social Research Institute (ESRI), 2018)
A new ESRI study, funded by the Health and Safety Authority (HSA), finds that job stress among employees in Ireland doubled from 8 per cent in 2010 to 17 per cent in 2015. However, the level of job stress in Ireland was still below the average for ten Western European countries in 2015 (19 per cent). The report uses two waves of a European-wide dataset, the European Working Conditions Survey, carried out in 2010 and 2015, to examine the working conditions that are associated with job stress.
Keywords: 330